TRAFFIC ACCIDENT POINT ANALYSIS, ON PRIMARY ARTERIAL ROAD-SUKABUMI DISTRICT - Paikun, Paikun; Faris, Wahyudi; Rozandi, Ardin (ASTONJADRO, 2021)
The increasing number of residents every year causes the need for transportation to also increase, this also occurs on the Sukabumi-Bogor Primary Arterial Road which is a road with a fairly high volume of traffic flow, in addition because the industrial center and tourism sector are located right on the national road, Insufficient geometric roads caused by the increasing number of vehicles is also a factor that affects the high number of traffic accidents along the Cibadak – Bogor Road. The purpose of this study was to analyze the characteristics of the accident-prone areas (blackspots) on the Jl. Surya Kencana, Pamuruyan Village, Cibadak District - Jl. Raya Ciutara, Pondok Kaso Landeuh Village, Parungkuda District. The method used in this study is the EAN (Equivalent Accident Number) method and the Cussum (Cumulative Summery) method. From the results of the weighting using the EAN method, it was identified that STA 1, STA 4, STA 5, and STA 6 were blackspots. Meanwhile, the Cussum method identified STA 1, STA 4, STA 5, STA 6, and STA 9 as blackspots. The right type of handling for accident-prone locations from the observations, among others, is making a thunder strip facility close to the zebra cross area to reduce vehicle speed and installing a safety fence on the shoulder of the road so as to minimize road crossings that directly cross the road without using zebra cross facilities.